"Reversing the trend": The role of mentoring in offender reentry. Issue 1 (2nd January 2018) - Stacer, Melissa J.; Roberts, Melinda R.
ABSTRACT: Faith-based programs are becoming more common in corrections, with most research examining offenders. Little attention has been paid to volunteers who work with offenders within these programs. In this project, 40 mentors who volunteered with a faith-based diversion and reentry program in southwestern Indiana were interviewed. Mentors revealed strong desires to help others, with religiosity driving their motivation to work with ex-offenders. Based on their mentoring experiences, mentors stated they were more sympathetic and their perspectives of ex-offenders and the conditions leading to crime had changed, including an increased awareness of problems related to reentry like housing, employment needs, and substance abuse.